Environment-friendly metal cutting fluid and preparation method thereof
By using polymer carbohydrate polymers such as mannan in metal cutting fluids, the problem of insufficient freezing resistance of existing cutting fluids is solved, and stable performance in cold environments is achieved.
Patent Information
- Application Number
- CN202411396492.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing metal cutting fluid has poor freezing resistance, resulting in a reduced performance in cold environments.
Polymer carbohydrate polymers, such as mannan, are used as components of the cutting fluid, and the antifreeze performance of the cutting fluid is improved through hydrogen bonding with water.
It significantly improves the freezing resistance of cutting fluid, allowing it to maintain stable performance in cold environments and avoid degradation in use.
Smart Images

Figure BDA0005073937370000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cutting fluids, and in particular relates to a green and environmentally friendly metal cutting fluid and a preparation method thereof. Background Art
[0002] Metal cutting fluid is a liquid used for cooling and lubrication during metal processing. It plays an important role in metal cutting, grinding, drilling and other processing processes. It can reduce the friction between the tool and the workpiece, extend the tool life, improve processing accuracy and surface finish, and also take away the heat generated during the cutting process to prevent the workpiece from affecting dimensional accuracy due to thermal deformation. Metal cutting fluid is usually composed of base oil, additives and water (for water-soluble cutting fluid). According to its composition and use, it can be divided into oil-based cutting fluid, semi-synthetic cutting fluid and fully synthetic cutting fluid. The correct selection and use of metal cutting fluid is crucial to improving production efficiency and product quality; among them, compared with traditional cutting fluid, environmentally friendly cutting fluid pays more attention to the impact on the environment, usually contains no or a small amount of harmful chemicals, is easy to biodegrade, and reduces potential harm to the health of operators and the environment. .
[0003] At present, what is studied more about environmentally friendly cutting fluid is how to increase its lubrication performance, cooling effect, and rust prevention ability. For example, CN118222350A uses organic amine compounds, organic acids, extreme pressure agents, surfactants, defoamers, corrosion inhibitors, bactericides, lubricants, and water as raw materials to obtain a kind of aluminum alloy water-based cutting fluid, which is environmentally friendly, green and environmentally friendly, and has no smoke and no odor during use, can effectively improve the on-site working environment, and ensure the health and safety of the employees' working environment. At the same time, the aluminum alloy water-based cutting fluid has the characteristics of excellent lubricity of semi-synthetic cutting fluid and cooling of fully synthetic cutting fluid, stable performance, and can significantly improve the service life of the tool. However, the cutting fluid may be in an environment with relatively low temperature during transportation, and being in this environment for a long time will affect the performance of the cutting fluid. At present, there is almost no research on the antifreeze performance of the cutting fluid. Summary of the invention
[0004] The first aspect of the present invention provides a green and environmentally friendly metal cutting fluid. The raw materials of the cutting fluid include, by mass fraction: 10-20% of polyol ester, 0.2-2% of high molecular sugar polymer, 20-45% of surfactant, 2-6% of silicate, 0.5-4% of rust inhibitor, 0.1-1% of bactericide, 0.1-1% of defoamer, and water supplemented to 100%.
[0005] As a preferred technical solution of the present invention, the raw materials of the cutting fluid include, by mass fraction: 15-18% polyol ester, 0.8-1.5% high molecular sugar polymer, 28-36% surfactant, 3-5% silicate, 1-3% rust inhibitor, 0.3-0.5% bactericide, 0.2-0.3% defoamer, and water is supplemented to 100%.
[0006] As a preferred technical solution of the present invention, the raw materials of the cutting fluid include, by mass fraction: 16% polyol ester, 1.2% high molecular sugar polymer, 33% surfactant, 4% silicate, 2% rust inhibitor, 0.4% bactericide, 0.25% defoamer, and water is supplemented to 100%.
[0007] The polyol ester has certain lubricity and biodegradability. As a preferred technical solution of the present invention, the polyol ester is selected from at least one of pentaerythritol oleate, trimethylolpropane carboxylate and neopentyl glycol dioleate, preferably pentaerythritol oleate.
[0008] There is basically no research on the antifreeze property of existing metal cutting fluids, but the inventors of the present invention have found through research that metal cutting fluids may be in a cold environment during transportation or before use, and the antifreeze property of existing metal cutting fluids is poor, so the performance of the cutting fluids after being in a cold environment is also reduced. Existing antifreeze agents are generally small molecule alcohol compounds, which have a low boiling point and are not suitable for use in the process of metal cutting fluids. This may also be because the existing cutting fluids cannot better break through the antifreeze property. The inventors unexpectedly found in the research that the use of high molecular weight carbohydrate polymers in the present invention can make the cutting fluid have excellent antifreeze properties.
[0009] As a preferred technical solution of the present invention, the high molecular weight carbohydrate polymer is selected from at least one of sucrose, fructose, glucose, mannan and mannose, preferably mannan.
[0010] The mannan in the present invention can be obtained from the market, preferably the konjac mannan purchased from Jinan Shenghe Chemical Co., Ltd., with the model number XH52801QJCHP.
[0011] The present invention has better antifreeze properties, especially when mannan is used. It is speculated that the reason is that mannan interacts with water and has excellent flexibility at low temperatures. At the same time, mannan interacts with water through a large number of hydrogen bonds, and the structure of the system is more stable. The flexibility and stability at low temperatures reduce the formation of ice crystals. Even if ice crystals are formed, when the cutting fluid returns to room temperature, its toughness makes the system have excellent resilience, which has little effect on the performance of the cutting fluid.
[0012] As a preferred technical solution of the present invention, the surfactant includes a modified surfactant and a cationic surfactant.
[0013] The preparation method of the modified surfactant comprises:
[0014] (1) N-dodecyl acrylamide and acrylonitrile are mixed to obtain a mixed material, and then chlorosulfonic acid is added dropwise to the mixed material under dynamic mixing, and after the addition is completed, the reaction is continued for 4-7 hours to obtain a reaction material A;
[0015] (2) adding sodium hydroxide aqueous solution to reaction material A so that the pH of the system is 10-12 to obtain reaction material B;
[0016] (3) The reaction material B is subjected to vacuum rotary evaporation to remove water, and then vacuum dried to obtain a modified surfactant.
[0017] The inventors have found that the use of the modified surfactant in the present invention can not only increase the lubricity of the cutting fluid, but also increase the resistance of the cutting fluid to hard water. This may be because the long alkyl chains in the modified surfactant can prevent the high-molecular sugar polymers from interacting with each other to form large molecules that affect the lubricity of the cutting fluid. At the same time, the imine group and the sulfonate at the tail end formed in the modified surfactant are less sensitive to metal ions, which is beneficial to improving the resistance of the cutting fluid to hard water.
[0018] As a preferred technical solution of the present invention, the molar ratio of N-dodecyl acrylamide to acrylonitrile is 1:(1-1.5).
[0019] As a preferred technical solution of the present invention, the conditions for the dynamic mixing include: a temperature of 20-30° C. and a rotation speed of 200-400 rpm.
[0020] As a preferred technical solution of the present invention, the dropping is completed within 1-1.5 hours.
[0021] As a preferred technical solution of the present invention, the concentration of the sodium hydroxide aqueous solution is 20-40wt%.
[0022] As a preferred technical solution of the present invention, the temperature of the vacuum rotary evaporation to remove water is 75-85°C.
[0023] As a preferred technical solution of the present invention, the vacuum drying conditions are: vacuum degree 0.06-0.085Mpa, temperature 70-80°C, and time 12-20h.
[0024] As a preferred technical solution of the present invention, the preparation method of the modified surfactant comprises:
[0025] (1) mixing N-dodecyl acrylamide and acrylonitrile at a molar ratio of 1:(1-1.5) to obtain a mixed material, then adding chlorosulfonic acid to the mixed material at a temperature of 20-30° C. and a rotation speed of 200-400 rpm, controlling the chlorosulfonic acid to react for 1-1.5 hours, and continuing the reaction for 4-7 hours after the addition of chlorosulfonic acid is completed to obtain a reaction material A;
[0026] (2) adding a sodium hydroxide aqueous solution with a concentration of 20-40 wt % to the reaction material A so that the pH of the system is 10-12 to obtain a reaction material B;
[0027] (3) The reaction material B is subjected to vacuum rotary evaporation at 75-85° C. to remove water, and then vacuum dried for 12-20 h at a vacuum degree of 0.06-0.085 MPa and a temperature of 70-80° C. to obtain a modified surfactant.
[0028] As a preferred technical solution of the present invention, the mass ratio of the modified surfactant to the cationic surfactant is 1:(0.5-1), preferably 1:(0.6-0.7).
[0029] As a preferred technical solution of the present invention, the surfactant is a modified surfactant and a cationic surfactant in a mass ratio of 1: (0.6-0.7).
[0030] The use of cationic surfactants in the present invention to interact with the specific modified surfactants in the present invention can better increase the lubricity of the cutting fluid, which may be because the end of the modified surfactant is an anionic surfactant, which interacts with the cationic surfactant and can better form micelles in the system, and can form a lubricating film more quickly on the surface of the substrate.
[0031] As a preferred technical solution of the present invention, the cationic surfactant is selected from imidazoline quaternary ammonium salt and / or long carbon chain quaternary ammonium salt, preferably imidazoline quaternary ammonium salt.
[0032] As a preferred technical solution of the present invention, the imidazoline quaternary ammonium salt is selected from eleostearic acid imidazoline quaternary ammonium salt and / or castor oil rosin imidazoline quaternary ammonium salt, preferably eleostearic acid imidazoline quaternary ammonium salt.
[0033] In the present invention, the inventors unexpectedly discovered that the use of imidazoline quaternary ammonium salt cationic surfactants can further increase the rust resistance of the cutting fluid, probably because the imidazoline group can inhibit the formation of free radicals in high molecular weight carbohydrate polymers to reduce the rust resistance of the cutting fluid.
[0034] Adding silicate in the present invention can further increase the hard water resistance of the cutting fluid. It is speculated that this is because under the synergistic effect of the modified surfactant, the Si-O- in the silicate is not sensitive to the reaction with the metal ions, and the cations in the silicate can react with the modified surfactant.
[0035] As a preferred technical solution of the present invention, the silicate is selected from inorganic silicates and / or organic silicates.
[0036] As a preferred technical solution of the present invention, the inorganic silicate is selected from at least one of sodium silicate, potassium silicate, sodium metasilicate and potassium metasilicate.
[0037] As a preferred technical solution of the present invention, the organic silicate is selected from potassium propyl silicate and / or sodium propyl silicate.
[0038] The inventors of the present invention have found through experimental research that the use of organic silicates can not only increase the resistance of the cutting fluid to hard water, but also improve to a certain extent the defect of high molecular sugar polymers that reduces the lubrication performance of the cutting fluid. This may be because the alkyl chains contained in organic silicates can prevent the high molecular sugar polymers from forming a gel in water, and organic silicates also increase the rust resistance of the cutting fluid to a certain extent.
[0039] As a preferred technical solution of the present invention, the rust inhibitor is selected from at least one of boric acid, sebacic acid and benzotriazole, preferably benzotriazole.
[0040] As a preferred technical solution of the present invention, at least one of dicyclohexylamine, oxadiazine, thiothiocarb and difenoconazole is used.
[0041] The defoamer in the present invention may be a conventional polyether defoamer and / or silicone defoamer in the art, such as polyether defoamer PPG-1000.
[0042] The second aspect of the present invention provides a method for preparing the green and environmentally friendly metal cutting fluid according to the first aspect of the present invention, the preparation method comprising:
[0043] Add 1 / 3 to 1 / 2 parts by mass of surfactant and high molecular sugar polymer to polyol ester and heat to 50-60°C, stir for 20-40 minutes and then stop heating, add silicate, rust inhibitor, bactericide, defoamer and water at 20-30°C and continue stirring for 20-30 minutes, then add the remaining surfactant and stir for 20-40 minutes to obtain a green and environmentally friendly metal cutting fluid.
[0044] Compared with the prior art, the present invention has at least the following beneficial effects:
[0045] 1. The cutting fluid of the present invention has excellent lubrication and wear resistance, which can reduce the friction between the tool and the workpiece, prolong the tool life, and improve the finish of the machined surface. In addition, the cutting fluid can also take away the heat generated during the machining process, reduce the temperature of the workpiece and the tool, thereby improving the machining efficiency and precision;
[0046] 2. The cutting fluid of the present invention has excellent rust resistance, which can ensure the surface quality of the workpiece during the processing and storage after processing, and avoid economic losses and scrapping of the workpiece caused by rust;
[0047] 3. The cutting fluid of the present invention has excellent antifreeze properties and can be stably stored in a cold environment;
[0048] 4. The cutting fluid of the present invention has excellent resistance to hard water, ensuring that it can remain stable under hard water conditions and is not easy to react with minerals such as calcium and magnesium in water to form precipitation, thereby ensuring the continued effectiveness of its lubrication and cooling properties. DETAILED DESCRIPTION
[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] In the following embodiments:
[0051] Konjac mannan was purchased from Jinan Shenghe Chemical Co., Ltd., model number is XH52801QJCHP
[0052] Example 1
[0053] Preparation of modified surfactants:
[0054] (1) N-dodecyl acrylamide and acrylonitrile are mixed at a molar ratio of 1:1.2 to obtain a mixed material, and then chlorosulfonic acid is added dropwise to the mixed material at a temperature of 25° C. and a rotation speed of 300 rpm, and the chlorosulfonic acid is controlled for 1.2 hours. After the addition of chlorosulfonic acid is completed, the reaction is continued for 5 hours to obtain a reaction material A;
[0055] (2) adding a 28 wt % sodium hydroxide aqueous solution to the reaction material A so that the pH of the system is 11.4 to obtain a reaction material B;
[0056] (3) The reaction material B was subjected to vacuum rotary evaporation at 80° C. to remove water, and then vacuum dried for 18 h at a vacuum degree of 0.075 MPa and a temperature of 80° C. to obtain a modified surfactant.
[0057] Preparation of cutting fluid raw materials: by mass fraction, prepare: 16% pentaerythritol oleate, 1.2% konjac mannan, 33% surfactant (modified surfactant and eleostearic acid imidazoline quaternary ammonium salt with a mass ratio of 1:0.65), 4% potassium propyl silicate, 2% benzotriazole,
[0058] 0.4% of azodiazole, 0.25% of defoamer (polyether defoamer PPG-1000), and water added to 100%.
[0059] Preparation of cutting fluid: Add 1 / 2 mass part of surfactant and konjac mannan to pentaerythritol oleate and heat to 55°C. Stir for 30 minutes and then stop heating. Add potassium propyl silicate, benzotriazole, oxadiazole, defoamer and water at 25°C and continue stirring for 25 minutes. Then add the remaining surfactant and stir for 30 minutes to obtain a green and environmentally friendly metal cutting fluid.
[0060] Example 2
[0061] Preparation of modified surfactants:
[0062] (1) N-dodecyl acrylamide and acrylonitrile are mixed at a molar ratio of 1:1.5 to obtain a mixed material, and then chlorosulfonic acid is added dropwise to the mixed material at a temperature of 25° C. and a rotation speed of 300 rpm, and the chlorosulfonic acid is controlled for 1.5 hours. After the addition of chlorosulfonic acid is completed, the reaction is continued for 4 hours to obtain a reaction material A;
[0063] (2) adding a 30 wt % sodium hydroxide aqueous solution to the reaction material A so that the pH of the system is 12 to obtain a reaction material B;
[0064] (3) The reaction material B was subjected to vacuum rotary evaporation at 80° C. to remove water, and then vacuum dried at a vacuum degree of 0.75 MPa and a temperature of 72° C. for 20 h to obtain a modified surfactant.
[0065] Preparation of cutting fluid raw materials: by mass fraction, prepare: 12% pentaerythritol oleate, 0.5% konjac mannan, 35% surfactant (modified surfactant and eleostearic acid imidazoline quaternary ammonium salt in a mass ratio of 1: (0.6-0.7)), 2% propyl potassium silicate, 1.5% benzotriazole, 0.2% oxadiazine, 0.3% defoamer (polyether defoamer PPG-1000), and add water to 100%.
[0066] Preparation of cutting fluid: Add 1 / 2 mass part of surfactant and konjac mannan to pentaerythritol oleate and heat to 60°C. Stir for 20 minutes and then stop heating. Add potassium propyl silicate, benzotriazole, oxadiazole, defoamer and water at 25°C and continue stirring for 30 minutes. Then add the remaining surfactant and stir for 30 minutes to obtain a green and environmentally friendly metal cutting fluid.
[0067] Example 3
[0068] Preparation of modified surfactants:
[0069] (1) N-dodecyl acrylamide and acrylonitrile are mixed at a molar ratio of 1:1.2 to obtain a mixed material, and then chlorosulfonic acid is added dropwise to the mixed material at a temperature of 25° C. and a rotation speed of 300 rpm, and the chlorosulfonic acid is controlled for 1.2 hours. After the addition of chlorosulfonic acid is completed, the reaction is continued for 5 hours to obtain a reaction material A;
[0070] (2) adding a 28 wt % sodium hydroxide aqueous solution to the reaction material A so that the pH of the system is 11.4 to obtain a reaction material B;
[0071] (3) The reaction material B was subjected to vacuum rotary evaporation at 80° C. to remove water, and then vacuum dried for 18 h at a vacuum degree of 0.075 MPa and a temperature of 80° C. to obtain a modified surfactant.
[0072] Preparation of cutting fluid raw materials: by mass fraction, prepare: 20% pentaerythritol oleate, 2% konjac mannan, 35% surfactant (modified surfactant and tung oil acid imidazoline quaternary ammonium salt in a mass ratio of 1:0.65), 6% propyl potassium silicate, 1% benzotriazole, 0.5% oxadiazole, 0.25% defoamer (polyether defoamer PPG-1000), and add water to 100%.
[0073] Preparation of cutting fluid: Add 1 / 2 mass part of surfactant and konjac mannan to pentaerythritol oleate and heat to 55°C. Stir for 30 minutes and then stop heating. Add potassium propyl silicate, benzotriazole, oxadiazole, defoamer and water at 25°C and continue stirring for 25 minutes. Then add the remaining surfactant and stir for 30 minutes to obtain a green and environmentally friendly metal cutting fluid.
[0074] Comparative Example 1
[0075] The method according to Example 1 is different in that:
[0076] Ethylene glycol was used in place of konjac mannan.
[0077] Comparative Example 2
[0078] The method according to Example 1 is different in that:
[0079] The surfactant is the modified surfactant in Example 1.
[0080] Comparative Example 3
[0081] The method according to Example 1 is different in that:
[0082] The surfactant is the eleostearic acid imidazoline quaternary ammonium salt in Example 1.
[0083] Comparative Example 4
[0084] The method according to Example 1 is different in that:
[0085] Dodecyldimethylbenzyl ammonium chloride was used to replace eleostearic acid imidazoline quaternary ammonium salt.
[0086] Comparative Example 5
[0087] The method according to Example 1 is different in that:
[0088] Replace potassium propyl silicate with sodium silicate.
[0089] Performance Testing
[0090] 1. Lubricity test:
[0091] The maximum non-seizure load (P) of the cutting fluid in the embodiment and the comparative example was tested respectively with reference to GB / T 3142-2019. B / N), the larger the maximum no-seizure load is, the better the lubricity of the cutting fluid is.
[0092] 2. Rust resistance
[0093] The cutting fluids in the examples and comparative examples were subjected to a primary grey cast iron corrosion test and a red copper corrosion test with reference to GB / T 6144-1985.
[0094] 3. Antifreeze
[0095] Place the cutting fluid in an environment of -10±2℃ for 12h, then take it out and restore it to room temperature and shake it again to test its maximum no-seizure load (PB / N). Compared with the maximum no-seizure load (PB / N) of the cutting fluid before placement, calculate the reduction rate of its maximum no-seizure load (PB / N).
[0096] 4. Hard water resistance
[0097] The cutting fluids in the embodiment and the comparative example were respectively diluted with water having a hardness of 20 to a concentration of 5 wt % to obtain a dilution. The dilution was injected into a 100 mL measuring cylinder and allowed to stand at a temperature of 25°C ± 2°C for 1 h. If the dilution had no floating soap and the amount was 0 mL, it was qualified, otherwise it was unqualified.
[0098] The test results are shown in Table 1.
[0099]
[0100] It can be seen from the above performance test results that the cutting fluid of the present invention not only has excellent lubricity and rust resistance, but also has excellent antifreeze and hard water resistance.
[0101] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A green and environmentally friendly metal cutting fluid, characterized in that: Calculated by mass fraction, the raw materials of the cutting fluid include: 10-20% of polyol ester, 0.2-2% of high molecular sugar polymer, 20-45% of surfactant, 2-6% of silicate, 0.5-4% of rust inhibitor, 0.1-1% of bactericide, 0.1-1% of defoamer, and water supplemented to 100%.
2. The green and environmentally friendly metal cutting fluid according to claim 1, characterized in that: The polyol ester is selected from at least one of pentaerythritol oleate, trimethylolpropane carboxylate and neopentyl glycol dioleate.
3. The green and environmentally friendly metal cutting fluid according to claim 1, characterized in that: The high molecular weight carbohydrate polymer is at least one selected from sucrose, fructose, glucose, mannan and mannose.
4. The green and environmentally friendly metal cutting fluid according to claim 1, characterized in that: The surfactant includes a modified surfactant and a cationic surfactant; The preparation method of the modified surfactant comprises: (1) N-dodecyl acrylamide and acrylonitrile are mixed to obtain a mixed material, and then chlorosulfonic acid is added dropwise to the mixed material under dynamic mixing, and after the addition is completed, the reaction is continued for 4-7 hours to obtain a reaction material A; (2) adding sodium hydroxide aqueous solution to reaction material A so that the pH of the system is 10-12 to obtain reaction material B; (3) The reaction material B is subjected to vacuum rotary evaporation to remove water, and then vacuum dried to obtain a modified surfactant.
5. The green and environmentally friendly metal cutting fluid according to claim 4, characterized in that: The molar ratio of N-dodecyl acrylamide to acrylonitrile is 1:(1-1.5); the conditions of the dynamic mixing include: a temperature of 20-30° C. and a rotation speed of 200-400 rpm; and the dropping is completed within 1-1.5 hours.
6. The green and environmentally friendly metal cutting fluid according to claim 4, characterized in that: The mass ratio of the modified surfactant to the cationic surfactant is 1:(0.5-1), preferably 1:(0.6-0.7).
7. The green and environmentally friendly metal cutting fluid according to claim 4, characterized in that: The imidazoline quaternary ammonium salt is selected from eleostearic acid imidazoline quaternary ammonium salt and / or castor oil rosin imidazoline quaternary ammonium salt.
8. The green and environmentally friendly metal cutting fluid according to claim 1, characterized in that: The silicate is selected from inorganic silicates and / or organic silicates.
9. The green and environmentally friendly metal cutting fluid according to any one of claims 1 to 8, characterized in that: The rust inhibitor is selected from at least one of boric acid, sebacic acid and benzotriazole; and at least one of dicyclohexylamine, oxadiazine, thiothiocarbamide and difenoconazole.
10. A method for preparing the green and environmentally friendly metal cutting fluid according to any one of claims 1 to 9, characterized in that: The preparation method comprises: Add 1 / 3 to 1 / 2 parts by mass of surfactant and high molecular sugar polymer to polyol ester and heat to 50-60°C, stir for 20-40 minutes and then stop heating, add silicate, rust inhibitor, bactericide, defoamer and water at 20-30°C and continue stirring for 20-30 minutes, then add the remaining surfactant and stir for 20-40 minutes to obtain a green and environmentally friendly metal cutting fluid.
Citation Information
Patent Citations
Water-based cutting fluid for aluminum alloy and preparation method of water-based cutting fluid
CN118222350A